The Effect of Brain Gym on Improving Fine Motoric and Gross Motoric Skills in Pre-School Children - Sinaga, Elvina Sari; Mila Syari (International Journal of Public Health Excellence (IJPHE), 2022)
Preschoolers are a period of very rapid growth and development. Where this period is the golden age experienced by children and is a very unique phase of life. Brain development, fine and gross motor skills at this time really need attention for the development of children. The incidence of developmental disorders in children aged 3-17 years in the United States has increased from 5.76% in 2014 and 6.9% in 2016. This type of research is Quasi-experimental with the research design used one group pre test-post test with control design. Population and sample: all of Assa'adah's early childhood students are 22 preschoolers, that is then shared to in 2 group that is 11 children group intervention and 11 children group control. This research was conducted at Assa'adah Early Childhood Education. The collection method is observation using the SOP Brain Gym measuring instrument , to assess progress using the Developmental Pre Screening Questionnaire (KPSP). The results of the univariate study of fine motor skills and pre-test gross motor skills in the intervention group were 8 doubtful (72.73%), 1 (9.09%) suitable minority. Whereas in the control group the majority doubted 6 (54.55%), the minority agreed 2 (18.18%). Fine motor skills and gross motor skills post-test in the intervention group the majority matched 8 (72.73%), the minority doubted 3 (27.27%). Whereas in the control group the majority doubted 6 (54.55%), the minority agreed 2 (18.18%). Average bivariate results ability pretest motor rough and smooth children group intervention (7.90) while the average postest (9,35). Results test statistics with wilcoxon show p.s value 0.005<0.05 so that there is influence brain therapy gym on ability development gross motor skills of children. Researchers suggest for apply Brains Gym environment early childhood for further improve fine motor and gross motor in preschool children with good.